Engaging Black youth in depression and suicide prevention treatment within urban schools: study protocol for a randomized controlled pilot - Lindsey, Michael A.; Mufson, Laura; Vélez-Grau, Carolina; Grogan, Tracy; Wilson, Damali M.; Reliford, Aaron O.; Gunlicks-Stoessel, Meredith; Jaccard, James (Current controlled trials in cardiovascular medicine, 2024)
Background Depression continues to be an ongoing threat to adolescent well-being with Black adolescents being particularly vulnerable to greater burdens of depression as well as lower mental health service utilization. Black adolescents are likely to have untreated depression due to social network influences, varied perceptions of services and providers, or self-stigma associated with experiencing depressive symptoms. Furthermore, if or when treatment is initiated, low engagement and early termination are common. To address this gap, a trial is being conducted to preliminarily test the effectiveness of an engagement intervention targeting Black adolescents with depression in school mental health services in New York City. Methods A total of 60 Black middle and high school adolescents displaying depressive symptoms are equally randomized (based on school site) to the treatment arms. Both trial arms deliver Interpersonal Psychotherapy for Depressed Adolescents (IPT-A), a time-limited, evidence-based treatment for depression. Additionally, one arm pairs IPT-A with a brief, multi-level engagement intervention, the Making Connections Intervention (MCI), involving adolescents, caregivers, and clinicians. Outcomes of interest are group differences in depression and suicide ideation, adolescent and caregiver engagement, and mental health service use. Discussion This trial will serve as an efficacy assessment of the MCI among a sample of Black adolescent students with depressive symptoms. Clinical and implementation results will be used to inform future research to further test the MCI intervention in a larger sample. Trial registration Registered by ClinicalTrials.gov on May 3, 2019, identifier: NCT03940508.